Synthesis and characterizations of nanohybrids based on amino silane-graphene oxide decorated by zirconium oxide nanoparticles - Zerguine, Narimene; Altin, Yasin; Dahoun, Abdesselam; Bouhelal, Said (Elsevier Science Sa, 2024)
This study aims to synthesize graphene oxide using the modified Hummers method and subsequently functionalize the surface of graphene oxide with amino silane N-(b-aminoethyl)-c-aminopropyltrimethoxysilane (AEAPTMS), resulting in silane-graphene oxide (SGO). The surface of SGO is then decorated with zirconium oxide (ZrO2) nanoparticles, generating SGO-ZrO2 nanohybrids. All the synthetized materials GO, SGO and SGOZrO2 were subjected to various characterization techniques, including Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), Thermogravimetric analysis (TGA), Zeta potential measurement and Scanning electron microscope (SEM). The results revealed that GO nanosheets were decorated with ZrO2 nanoparticles through covalent bonding with AEAPTMS.
Keywords: Graphene oxide; Amino silane; Zirconium oxide; Nanohybrids